2012
DOI: 10.1186/1471-2199-13-8
|View full text |Cite
|
Sign up to set email alerts
|

EGF activates TTP expression by activation of ELK-1 and EGR-1 transcription factors

Abstract: BackgroundTristetraprolin (TTP) is a key mediator of processes such as inflammation resolution, the inhibition of autoimmunity and in cancer. It carries out this role by the binding and degradation of mRNA transcripts, thereby decreasing their half-life. Transcripts modulated by TTP encode proteins such as cytokines, pro-inflammatory agents and immediate-early response proteins. TTP can also modulate neoplastic phenotypes in many cancers. TTP is induced and functionally regulated by a spectrum of both pro- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Various transcription factors control the transcription of TTP [ 22 , 23 ]. Recently, the role of EGR1 has been highlighted in breast cancer cell model and HDAC inhibitors can induce this transcription factor [ 24 , 25 ]. EGR1 is also associated with an immediate/early gene expression response, consistent with the early induction of TTP observed upon TSA treatment ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various transcription factors control the transcription of TTP [ 22 , 23 ]. Recently, the role of EGR1 has been highlighted in breast cancer cell model and HDAC inhibitors can induce this transcription factor [ 24 , 25 ]. EGR1 is also associated with an immediate/early gene expression response, consistent with the early induction of TTP observed upon TSA treatment ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our findings suggest that the epigenetic events leading to TTP upregulation by HDAC inhibition do not occur on the TTP promoter itself, but at a different locus, e.g., a transcription factor(s) that regulates expression of TTP. In this context, EGR1 represents a good candidate based on its ability to increase TTP expression in breast cancer cells [ 24 ] and HDAC inhibitors can induce EGR1 expression [ 25 ]. EGR1 is a Cys2His2 zinc finger transcription factor, which binds GC rich region (5'-GNG TGG GCG-3') [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Xenopus, the expression pattern of beclin1, at stage 19 is partially similar to the expression of zfp36 with a distinctive speckled pattern along the neural fold (Bowes et al, 2010). Beclin-1 is involved in the activation of the autophagy pathway a process which is accompanied by an increase in ERK signaling (Florkowska et al, 2012;Martinez-Lopez et al, 2013). Because neural tube closure appears as being critically controlled by autophagy and apoptosis (Cecconi et al, 2008) it is therefore possible that zfp36 labelling along the neural folds represent a transient activation of zfp36 expression in cells undergoing apoptosis or autophagy.…”
Section: Origin Of Zfp36-positive Cells and Function In The Fusing Nementioning
confidence: 99%
“…Inhibitor studies involving inhibition of NF-kB, in the presence of IL-1b and LPS, have shown that TTP mRNA is a direct substrate of the NF-kB signaling pathway (King et al, 2009;Chen et al, 2013). Other signaling pathways include the protein kinase C (PKC) pathway, via transcription factor activating protein 2, which was shown to regulate TTP mRNA in the presence of a phorbol ester (Chen et al, 1998;Tan and Parker, 2003;Jalonen et al, 2007;Leppänen et al, 2008Leppänen et al, , 2010 and the epidermal growth factor pathway, via the transcription factor ETS domain-containing protein ELK-1 (Florkowska et al, 2012).…”
Section: Ttp Function: Multiple Levels Of Regulatory Controlmentioning
confidence: 99%